Penerapan Konsep Restorative Justice Pada Kasus Pelecehan Seksual (studi Penetapan Nomor 9/JN/2021/MS.Skm) - Via Susanti Via Susanti; Eza Aulia (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
The application of restorative justice based on Determination Number 9/JN/2021/MS.Skm is applied to cases of sexual harassment. In the case of sexual harassment the defendant and 3 (three) other defendants forced and threatened the victim to take turns harassing them. In this case, the judge determines that there is restorative justice in sexual harassment cases, where the defendant should be punished for the actions he committed to get a lesson and a deterrent effect. The consideration of the judge is to accept the existence of restorative justice in cases of sexual harassment and the judge makes legal findings that are not appropriate in the case. From this background, the authors put forward 2 problem formulations, namely the consideration of restorative justice applied to Designation Number 9/JN/2021/MS.Skm and the legal consequences of applying restorative justice to Determination Number 9/JN/2021/MS.Skm. This study uses a normative juridical method. When considering sexual harassment the judge made a legal discovery, the legal finding was inappropriate because sexual harassment is a serious case and violates human rights. Meanwhile, the legal consequences of implementing restorative justice do not have a deterrent effect for the defendant, because the defendant can repeat the same crime again. The conclusion is that in this case, the judge was wrong in making legal findings, because the legal findings from the judge could not be applied to cases of sexual harassment, legal findings were made when there was a legal vacuum, while sexual harassment had rules that governed it.